2004
DOI: 10.1126/science.1099962
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in NF-κB Signaling Control the Dynamics of Gene Expression

Abstract: Signaling by the transcription factor nuclear factor kappa B (NF-kappaB) involves its release from inhibitor kappa B (IkappaB) in the cytosol, followed by translocation into the nucleus. NF-kappaB regulation of IkappaBalpha transcription represents a delayed negative feedback loop that drives oscillations in NF-kappaB translocation. Single-cell time-lapse imaging and computational modeling of NF-kappaB (RelA) localization showed asynchronous oscillations following cell stimulation that decreased in frequency w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
1,138
3
10

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,103 publications
(1,234 citation statements)
references
References 28 publications
67
1,138
3
10
Order By: Relevance
“…Research using real-time single-cell imaging has shown NF!B shuttling in and out of the nucleus under an inflammatory stimulus such as TNF!, matched with firefly-luciferase activity [40]. Here we show that the data from a Gaussia luciferase reporter under the control of NF!B is a valid measure of the dynamics of transcriptional activity due to NF!B stimulation in a cell population.…”
Section: Discussionmentioning
confidence: 74%
“…Research using real-time single-cell imaging has shown NF!B shuttling in and out of the nucleus under an inflammatory stimulus such as TNF!, matched with firefly-luciferase activity [40]. Here we show that the data from a Gaussia luciferase reporter under the control of NF!B is a valid measure of the dynamics of transcriptional activity due to NF!B stimulation in a cell population.…”
Section: Discussionmentioning
confidence: 74%
“…The experimental results in Ref. [5] show only few periods of the oscillations, making it difficult to decide whether one deals with sustained or damped oscillations. The same may be said for the results in [2].…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
“…The three proteins Hes1, p53, and NF-κB are transcriptionally regulated by short negative feedback loops and actual experiments have revealed that their genes show an oscillatory expression [1,2,3,4,5]. In the vertebrate segmentation clock several cycling genes are involved in an oscillatory mechanism driving somite segmentation [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These initial studies utilized IkB-deficient cell lines and observed that continual application of TNF resulted in extended oscillations of NF-kB activity in IkBe À/À b À/À cells owing to the powerful negative feedback of NF-kBcontrolled IkBa expression. Similarly, overexpression of RelA and RelA-responsive IkBa by transient transfection resulted in oscillatory activity in single cells as revealed by video microscopy in single cells (Nelson et al, 2004), although the resulting increase in the green fluorescence protein-fusion effector molecules can alter the dynamic behavior . However, in wild-type cells, NF-kB activity is subject to other negative feedback mechanisms.…”
Section: Transcriptional Specificity As Determined By Nf-jb Dynamicsmentioning
confidence: 99%